The Influence Of Brand Image And Service Quality On Customer Loyalty Mediated By Consumer Satisfaction Coffee Products - Pratama, Mochammad Aditya Reza; Mardalis, Ahmad (Jurnal Mirai Management, 2024)
Introduction/Main Objectives: The study aims to know how customer satisfaction acted as the mediating factor among brand image and service quality also customer loyalty. Background Problems: The high demand for coffee products in Indonesia makes the competition for coffee products tighter, what influences customer loyalty in buying the coffee products offered. Novelty: This study is a crucial step in comprehending the dynamics of the coffe market in greater detail, particularly when considering important variables like brand image, customer satisfaction and service quality. Research Methods: quantitative methods were used with primary data sources in the preparation, the number of respondents obtained was 286. data processing techniques using SMARTPLS 3.0. Finding/Results: customer loyalty and satisfaction are positively impacted from brand image and service quality. Customer satisfaction is the mediating factor among brand image also service quality also the customer loyalty. Conclusion: to conclue the customer loyalty is possible if the satisfaction is established and customer satisfaction can occur if the perceived value of customer service quality is higher. Keywords: Brand Image, Service Quality, Customer Loyalty, Customer Satisfaction